Arsitektur Tradisional : Rumah Limasan di Desa Sojomerto Masih Melekat di Era Modern sebagai Warisan Budaya - Laila Haniatun Nasikah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Traditional Indonesian architecture is a cultural heritage that includes deep aesthetic, social and functional values. Limasan houses, as a form of traditional Javanese architecture, have become a symbol of cultural wealth and ancestral heritage that is rich in historical and philosophical values. Limasan houses can still be found in several rural areas, one of which is in Sojomerto Village, Kendal Regency, Central Java. Even though modern architecture has developed rapidly amidst rapid modernization, preserving Limasan houses faces various challenges, both from an economic, cultural and environmental perspective. The research used field observation methods, interviews with local residents, and literature study. The research results show that despite facing the challenges of contemporary developments, Rumah Limasan in Sojomerto still shows its existence as a cultural identity and reflects a balance between ancestral heritage and modern needs.